ETHICAL CONSIDERATIONS IN MANAGEMENT OF DIGITAL LITERACY AND INCLUSIVE EDUCATION IN PUBLIC SECONDARY SCHOOLS IN RIVERS STATE FOR SUSTAINABLE DEVELOPMENT (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study investigated ethical considerations in the management of digital literacy and inclusive education in public secondary schools in Rivers State for sustainable development. Two research questions and two hypotheses guided the study. Descriptive survey design was used in the study with a population of 8, 620 public secondary school teachers in Rivers State. A sample of 431 teachers representing 5% of the population was drawn through stratified random sampling technique. A questionnaire titled, “Ethical Considerations in the Management of digital Literacy and Inclusive Education Questionnaire (ECMDL & IEQ)” developed by the researcher was used for data collection. The instrument was well validated and the test of reliability via Cronbach Alpha method yielded a reliability index of 0.82. mean scores, standard deviation and rank order were used to analyse the research questions, while z-test was used to test the hypotheses at 0.05 level of significance. Results of the study revealed that ethical considerations in the management of digital literacy in public secondary schools in Rivers State include among others: digital divide; data privacy and security; accessibility and inclusion; and cyber security. While ethical considerations in the management of inclusive education include among others: access and equity; bias/discrimination; diversity and representation; and teacher training and support. Based on the findings, conclusion was drawn and the following recommendations among others were made: educators, government and stakeholders in secondary education must embrace the mindset of continuous improvement on ethical standards emerging from technological advancements and evolving pedagogical innovations.